Perbandingan Verifikasi Akurasi Posisi Pasien Radioterapi Secara Manual dan Semiotomatis Berbasis Citra DRR/EPID - SUSI NOFRIDIANITA; HERU PRASETIO; SUPRIYANTO A PAWIRO (Indonesian Journal of Cancer, 2016)
ABSTRACTRadiotherapy is one of common treatment modality for Nasopharyngeal Cancer. The development of intensity modulated radiotherapy (IMRT technique) gives satisfactory results in the nasopharyngeal cancer treatment, both clinically and dosimetry. IMRT can reduce the effects of acute and chronic, with a maximum dose coverage to the tumor and minimal dose to the organ or normal tissue surrounding target value. The purpose of this study is to compare theaccuracy of patient positioning verification of Nasopharyngeal Cancer IMRT with DRR / EPID image registration. Retrospective data analysis of the AP and Lateral projections DRR and EPID images 35 patients (140 images) were then manually verified by simulative applied fusion semiautomatic with FIJI program. FIJI program improved the image quality of the DRR and EPID to facilitate the image registration. Results of this study shows no statistically significantdifference between the manual verification and semiautomatic fusion method of nasopharyngeal cancer patients, but there is a tendency that the semiautomatic method with FIJI program provides verification geometry radiotherapy better a result than manual methods.ABSTRAKTeknik Intensity Modulated Radiotherapy (IMRT) dapat mengurangi efek akut dan kronik, dengan cakupan dosis maksimal pada tumor dan dosis minimal pada organ/jaringan sehat di sekitarnya. Tujuan dari penelitian ini adalah untuk mengetahui perbandingan verifikasi akurasi posisi pasien IMRT Kanker Nasofaring dengan registrasi citra DRR/ EPID. Analisis data retrospektif terhadap citra DRR/EPID dari 35 pasien proyeksi AP dan Lateral (140 citra) yang telah diverifikasi secara manual kemudian secara simulatif diterapkan metode fusi semiotomatis dengan program FIJI. Penggunaan program FIJI dapat memperbaiki kualitas citra DRR/EPID sehingga memudahkan dalam verifikasi geometri radioterapi. Hasil penelitian ini secara statistik menunjukkan tidak terdapat perbedaan antara verifikasi manual denganmetode fusi pada radioterapi pasien kanker nasofaring, namun secara deskriptif terdapat kecenderungan bahwa metode fusi dengan program FIJI memberikan verifikasi geometri radioterapi yang lebih baik dibandingkan metode manual.